2019
DOI: 10.48550/arxiv.1901.10233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconstruction of 3D Porous Media From 2D Slices

Abstract: In many branches of earth sciences, the problem of rock study on the micro-level arises. However, a significant number of representative samples is not always feasible. Thus the problem of the generation of samples with similar properties becomes actual. In this paper, we propose a novel deep learning architecture for three-dimensional porous media reconstruction from two-dimensional slices. We fit a distribution on all possible three-dimensional structures of a specific type based on the given dataset of samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Mosser et al 13 proposed to use average grain size and chord length as the minimum training image size. However, a representative elementary size (RES) analysis should be carried out for heterogeneous and complex samples to find an adequate training image size 34 . RES analysis is a methodology to determine the smallest size of a system that is large enough to capture the system's heterogeneity as a whole 51 .…”
Section: Reconstruction Of Representative Microstructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Mosser et al 13 proposed to use average grain size and chord length as the minimum training image size. However, a representative elementary size (RES) analysis should be carried out for heterogeneous and complex samples to find an adequate training image size 34 . RES analysis is a methodology to determine the smallest size of a system that is large enough to capture the system's heterogeneity as a whole 51 .…”
Section: Reconstruction Of Representative Microstructuresmentioning
confidence: 99%
“…Several studies have shown the successful application of these techniques for 2D and 3D 13,29,30 . Notably, a growing body of literature has recently investigated 2D to 3D image reconstructions intending to infer 3D morphological and structural properties using features extracted from 2D images in specific orientations [31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of such loss is that it can be easily applied to 3D textures. Previous works [27,39] on synthesizing 3D porous material used GANs-based methods with 3D convolutional layers inside a generator and a discriminator. However, they trained separate models for each texture.…”
Section: Related Workmentioning
confidence: 99%
“…We apply our method to 3D texture-like porous media structures which is a real-world problem from Digital Rock Physics. Synthesis of porous structures plays an important role [39] because an assessment of the variability in the inherent material properties is often experimentally not feasible. Moreover, usually it is necessary to acquire a number of representative samples of the void-solid structure.…”
Section: Introductionmentioning
confidence: 99%
“…Mosser et al (2017) firstly used DCGANs to reconstruct 3D porous structures of sandstone and carbonate. After their ground-breaking work, DCGANs rapidly swept the community and became an important approach for digital rock reconstruction (Mosser et al, 2018;Liu et al, 2019;Volkhonskiy et al, 2019;Valsecchi et al, 2020). Inspired by this, various GAN models have also been used, including but not limited to conditional GAN (Feng et al, 2019;Volkhonskiy et al, 2019), style GAN (Fokina et al, 2020), progressively growing GAN (Zheng and Zhang, 2020), Bicycle GAN (Feng, et al, 2020), as well as some hybrid models combining variational autoencoder and DCGAN (Shams et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%